The daily Covid-19 information from the public's lens - Ahmad, Zeti Azreen; Buyong, Mazni; Souket, Rizwanah (Asian Media Information and Communication Centre (AMIC), 2022)
COVID-19 pandemic has imposed an unprecedented impact on people around the globe and Malaysia is no exception.The battle to fight the unseen virus came along with infodemic: a massive amount of information that includes a mixture of true and false narratives that makes intervention efforts even more complicated. The role of the Ministry of Health (MoH) has been instrumental in managing the pandemic and infodemic in Malaysia. The MoH has never failed to update the public and the media through press conferences and press statements since the first few cases of COVID-19 were reported in early January 2020. Daily statistics of COVID-19 cases have been uploaded in MoH’s website and social media platforms. In a recent development, details of COVID-19 cases are now reported in a new website known as CovidNow. This research argues that living with a fatal pathogen such as SARS-CoV-2 requires every person to have access to trustworthy information. Furthermore, understanding of the information is fundamental as it empowers the public to make informed decisions to save lives. This study argues that effective public communication of science related information such as COVID-19 is essential to contain transmission of the disease particularly when the country is preparing to enter the endemic stage. However, the publics’ ability to interpret scientific information has not received adequate attention in the literature. This study explores whether the information shared by the Ministry of Health (MoH) were perceived to be reliable, trustworthy and subsequently improved the publics’ practices in terms of adhering to the standard operating procedure (SOP) to prevent COVID-19. More than 1000 responses were received from a survey that was conducted online. The study found that information about COVID-19 was mainly obtained through MySejahtera apps and WhatsApp. Generally, the publics’ perception of the daily update of COVID-19 has been very positive. The information shared by the MoH was perceived useful, clear, reliable and trustworthy by the publics and subsequently resulted in high compliance among the publics towards the SOPs.